1995
DOI: 10.1093/nar/23.5.849
|View full text |Cite
|
Sign up to set email alerts
|

Novel system for analysis of group I 3' splice site reactions based on functionaltrans-interaction of the P1/P10 reaction helix with the ribozyme's catalytic core

Abstract: A group I intron from a bacterial tRNA precursor has been converted into an RNA enzyme that catalyzes the efficient polymerization of oligoribonucleotide analogs of tRNA exons using a reaction scheme consisting of multiple cycles of reverse and forward exon ligation reactions. Here, we present results showing that this system represents a novel and useful tool for the analysis of 3' splice site reactions of group I ribozymes. First, analysis of variant substrates containing base substitutions in group I second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 38 publications
(38 reference statements)
2
13
0
Order By: Relevance
“…The trans-splicing activity of the blind Azoarcus ribozyme is in accordance with a previous study that demonstrated that if the IGS were disarticulated from the catalytic core on a separate fragment, and then an effectively full-length ribozyme could polymerize oligonucleotide sequences on its 3´ end (Chowrira et al, 1995). In that study an exogenous IGS (termed the external guide sequence, or EGS) required the GUG from P1 plus an additional 7 nt from P10 of the natural bacterial intron.…”
Section: Evolutionary Implicationssupporting
confidence: 87%
See 2 more Smart Citations
“…The trans-splicing activity of the blind Azoarcus ribozyme is in accordance with a previous study that demonstrated that if the IGS were disarticulated from the catalytic core on a separate fragment, and then an effectively full-length ribozyme could polymerize oligonucleotide sequences on its 3´ end (Chowrira et al, 1995). In that study an exogenous IGS (termed the external guide sequence, or EGS) required the GUG from P1 plus an additional 7 nt from P10 of the natural bacterial intron.…”
Section: Evolutionary Implicationssupporting
confidence: 87%
“…Second, it is behaving as an exogenous IGS, bringing a requisite GUG into the catalytic core of a ribozyme complex. The multifunctional fragment containing the exogenous IGS is held likely in place by tertiary interactions (Chowrira et al, 1995) such as those postulated in Figure 9. And third, it is being utilized as a substrate for recombination, in which its CAU sequence (or a lowerror variant) is targeted by an IGS for transesterification to another RNA molecule.…”
Section: Multifunctionality In Catalytic Rnasmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies used high Mg 2+ concentrations (10-100 mM) and high temperature (48°C-60°C, with the optimum around 60°C) (Chowrira et al 1993(Chowrira et al , 1995Tanner and Cech 1996;Kuo et al 1999;Chauhan et al 2005;Hayden et al 2005;Sinan et al 2011). Under these conditions, the Azoarcus ribozyme is able to catalyze an impressive variety of transreactions.…”
Section: Discussionmentioning
confidence: 99%
“…Under these conditions, the Azoarcus ribozyme is able to catalyze an impressive variety of transreactions. By repetitively splicing a substrate the Azoarcus ribozyme can cause an effect like RNA polymerization (Chowrira et al 1993(Chowrira et al , 1995. By trans-ligating RNA oligomers the Azoarcus ribozyme can create active ribozymes from inactive ribozyme fragments (Hayden et al 2005).…”
Section: Discussionmentioning
confidence: 99%